THE RISK FACTORS OF DIABETES MELLITUS IN ADOLESCENT SENIOR HIGH SCHOOL IN MALANG CITY - Dyah Widodo; Ekowati Retnaningtyas; Ibnu Fajar (Universitas Airlangga, 2017)
Introduction: Diabetes mellitus is a disease caused by a hormonal disorder that affects insulin. 5.7% of the total population of Indonesia, including teenagers is a big challenge for the health sector to do the step in anticipation of the complexity of health problems caused by diabetes mellitus in Indonesia. This study aims to analyze the risk factors of diabetes mellitus in adolescent senior high school in the city of Malang. Method: This research was correlational research design, sampled in this study was partly teenagers is high school class in Malang city area drawn at random sampling with a large sample of 375 respondents. Research conducted at government senior high school 6 and 9 (SMU Negeri 6 and SMU Negeri 9) in the city of Malang, in May-August, 2011. Data collection techniques using questionnaires; measurements: weight, height, abdominal circumference/waist, blood pressure and food consumption survey (Recording of Present Food Intake) of the diet for three days. Data was analyzed by descriptive and analytic Spearman Rho correlation with alpha 0.05. Result:  The results showed that a BMI (body mass index) and waist circumference (central obesity) related to the risk of diabetes mellitus in teens senior high school in Malang with 0.000 p-values < α 0.05. However, there is no relationship between blood pressure, physical activity, frequency of fruit and vegetable consumption, family history of diabetes mellitus and the risk of diabetes mellitus in teens senior high school in Malang. Discussion: Recommended for teens to pay attention to healthy eating and balanced, in order to awake the ideal body weight and abdominal circumference are normal, so that avoid the risk of diabetes mellitus.